Aspek Kecemasan (Anxitas) dalam Puisi Al-Kulira Karya Nazek Al-Malaika (Kajian Psikologi Sastra) - Murisatin Nikmah; Mochammad Faizun (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
The purpose of this study to find out the anxiety aspect in literary works. The main data source of this study is Nazek Al-Malaika's Al-Kulira poem, one of the poems based on the emotional effects of the cholera outbreak in Egypt in 1947. This study uses qualitative descriptive method by describing and analyzing the form and meaning contained in the poem Al-Kulira by nazek Al-Malaika then identify which sentences or lines of poetry correspond to the aspect of anxiety and relate to the theory of psychoanalytic personality sigmund Freud. The result of this study is Freud distinguished three structures or agents in human psychic life ,